PENYULUHAN EFEK SAMPING DEPO PROGESTIN DI GAMPONG GAJAH KECAMATAN MUTIARA KECAMATAN MUTIARA KABUPATEN PIDIE - Salamah Salamah; Zaitun Zaitun; Amelia Faris (COVIT (Community Service of Health), 2022)
Injecting contraceptives have good and bad effects for users, the good effects include being very effective and having a long-term pregnancy prevention effect, no effect on marital relations, does not contain estrogen so it has no serious impact on heart disease and blood clotting disorders, has no effect on breast milk, preventing endometrial cancer and ectopic pregnancy, reducing the incidence of benign breast disease, preventing some pelvic inflammatory diseases, reducing crescentic anemia crises, and few side effects. Other impacts include disruption of menstrual patterns, delays in returning to fertility (disturbances of menstrual problems), weight gain, emotional instability, depression, and does not guarantee protection against sexually transmitted infections. Rapid population growth will affect life in society. To prevent this problem, the government held a family planning program. The use of injectable birth control is the method most in demand by the public to date. The purpose of this community service is to increase the knowledge of PUS about injecting contraceptives as protection against pregnancy. This service method uses counseling (lectures and questions and answers) about the side effects of Depo progestin injection type contraception. Conclusion: There is an increase in the knowledge of injecting family planning acceptors about the side effects of Depo Progestin injection family planning. Suggestions from the author are to carry out counseling activities more often about the various types of family planning and their side effects, especially progestin depot injections, considering that they are in great demand by PUS and have no effect on milk production for breastfeeding mothers. Keywords: Counseling, Side Effects of Depro Pogestin